2009
DOI: 10.1080/00207450802480044
|View full text |Cite
|
Sign up to set email alerts
|

Mollaret Meningitis may be Caused by Reactivation of Latent Cerebral Toxoplasmosis

Abstract: Mollaret meningitis (MM) occurs mainly in females and is characterized by recurrent episodes of headache, transient neurological abnormalities, and the cerebrospinal fluid containing mononuclear cells. HSV-2 was usually identified as the causative agent. Recently, we found that recurrent headaches in non-HIV-infected subjects were due to acquired cerebral toxoplasmosis (CT). The aim of the study was therefore to focus on molecular pathomechanisms that may lead to reactivation of latent CT and manifest as MM. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 195 publications
(208 reference statements)
0
3
0
Order By: Relevance
“…Calcified cavernous hemangioma in the left occipital region had also been described in a 45-year-old woman with frequent episodes of disorientation, confusion, agitation, delusion, and multiple seizure-type changes in EEG. One may suggest that these and other cases of calcifications in the brain were the result of reactivation of latent CT (Prandota, 2009a(Prandota, , 2009b(Prandota, , 2009c. Also, reactivation of latent CT was probably associated with the development of anaplastic ependymoma in a 30-year-old woman hospitalized because of a one week history of persistent right-sided retro-orbital pain and blurred vision, and diagnosed with IIH (Rourke, Davies, & Samandouras, 2008).…”
Section: Anatomopathologic Studies Of Cerebral Lesions In Children Wimentioning
confidence: 93%
“…Calcified cavernous hemangioma in the left occipital region had also been described in a 45-year-old woman with frequent episodes of disorientation, confusion, agitation, delusion, and multiple seizure-type changes in EEG. One may suggest that these and other cases of calcifications in the brain were the result of reactivation of latent CT (Prandota, 2009a(Prandota, , 2009b(Prandota, , 2009c. Also, reactivation of latent CT was probably associated with the development of anaplastic ependymoma in a 30-year-old woman hospitalized because of a one week history of persistent right-sided retro-orbital pain and blurred vision, and diagnosed with IIH (Rourke, Davies, & Samandouras, 2008).…”
Section: Anatomopathologic Studies Of Cerebral Lesions In Children Wimentioning
confidence: 93%
“…In vitro studies that mimic an immunocompromised state have shown that the conversion occurs within 1 week regardless of the age of the brain cysts (5). In immunocompetent hosts, the presence of cysts caused by T. gondii (referred to here as "T. gondii cysts") in the brain seems to be associated with various neurological disorders (27), including cryptogenic epilepsy (37), migraine (25), schizophrenia (38), Malloret meningitis (26), and affective (36) and behavioral (11) disorders.…”
mentioning
confidence: 99%
“…In addition, pyrin appeared to have both inhibitory and potentiating effects on IL-1β production and played a role in regulating NF-κB activation and apoptosis [105,106] . It was suggested that in patients with FMF T. gondii infection plays an important role in the pathogenesis of Mollaret meningitis [107] . Moreover, in human astroglia cells and in murine mast cells infected with T. gondii tachyzoites, the parasite induced upregulation of profibrotic factors, such as matrix metalloproteinase-2 and -9 (MMPs) via Erk1/2-NF-κB pathway [108] , and MMPs are a family of the extracellular matrix-degrading enzymes that are generally synthesized and secreted as latent soluble enzymes requiring activation in the extracellular space [109] .…”
Section: Cryptogenic Liver Cirrhosis (Clc)mentioning
confidence: 99%